2003
DOI: 10.1161/01.hyp.0000097547.35570.70
|View full text |Cite
|
Sign up to set email alerts
|

Celiprolol Activates eNOS Through the PI3K-Akt Pathway and Inhibits VCAM-1 Via NF-κB Induced by Oxidative Stress

Abstract: Abstract-Vascular cell adhesion molecule-1 (VCAM-1) and reactive oxygen species play critical roles in early atherogenesis, and nitric oxide (NO) is an important regulator of the cardiovascular system. Although celiprolol, a specific ␤ 1 -antagonist with weak ␤ 2 -agonistic action, stimulates endothelial nitric oxide synthase (eNOS) production, the mechanisms remain to be determined. Because it was recently reported that phosphatidylinositol 3-kinase (PI3K) and its downstream effector Akt are implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 38 publications
(40 reference statements)
4
71
0
Order By: Relevance
“…Celiprolol was also reported to activate eNOS through the PI3K-Akt signaling pathway. 18 Conversely, the impact on PIN may be a specific effect of ␤ 1 -blockers. It was reported that an association exists between nNOS decrease in the hypothalamus and enhanced sympathetic tone in rats with heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Celiprolol was also reported to activate eNOS through the PI3K-Akt signaling pathway. 18 Conversely, the impact on PIN may be a specific effect of ␤ 1 -blockers. It was reported that an association exists between nNOS decrease in the hypothalamus and enhanced sympathetic tone in rats with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…sis. 16,18 Expression of these proteins was detected by use of the diaminobenzidine method and quantified by densitometry.…”
Section: No Measurementmentioning
confidence: 99%
“…6,17 PCR was done using synthetic oligonucleotide primers as reported previously. 6,17 The numbers of PCR cycles for the 12 genes examined were as follows: eNOS, 30; iNOS, 31; NAD(P)H oxidase p22phox, 36; p47phox, 32; gp91phox, 33; LOX-1, 38; MR, 32; aldosterone synthase (CYP11B2), 31; sarcoplasmic reticulum Ca 2ϩ -ATPase (SERCA2), 32; transforming growth factor (TGF)-␤1, 32; type I collagen, 27; and GAPDH, 22.…”
Section: Quantification Of Mrna Using Rt-pcrmentioning
confidence: 99%
“…11,17 Activity of p65NF-B, PKC␤II, c-Src, p44/p42 Extracellular Signal-Regulated Kinase, p70 S6 Kinase, eNOS, and Akt p65NF-B, PKC␤II, c-Src, p44/p42 extracellular signal-regulated kinase (ERK), p70 S6 kinase (p70S6K), eNOS, and Akt phosphorylation was measured as described in detail previously. 6,14 …”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation